Study on statistical correlation exploitation in distributed video coding - Sun, Jin. (2012)
Distributed coding is a new paradigm for video compression, based on Slepian and Wolf’s and Wyner and Ziv’s information-theoretic results from the 1970s. Distributed video coding (DVC), i.e., lossy compression with receiver side information, enables low-complexity video encoding where the bulk of the computation is shifted to the decoder.However, compared to conventional motion-compensated interframe coding, distributed video coding (DVC) has a worse rate-distortion performance according to the existing works. The most important reason is that it is much more difficult to fully exploit the temporal correlation of the video sources by using motion estimation at the decoder where less information is available. Another reason is that conventional video coding adopt the entropy approaching tools to exploit the statistical correlation among the coefficients while existing DVC utilize only channel coding based Slepian-Wolf coding to exploit the statistical correlation.